2019
DOI: 10.1002/wene.362
|View full text |Cite
|
Sign up to set email alerts
|

Risk mitigation in the electricity market driven by new renewable energy sources

Abstract: An important indicator of supply and demand uncertainty on electricity markets is risk premium (RP), an integral part of electricity price. The level of RP is describing the risk the market actors expect in the future due to the market uncertainties. With the electricity market price behavior rapidly changing, the rising market supply uncertainty is increasing the volatility of RP. To better understand this behavior, power market participants need new models that will efficiently use the information available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Moreover, Koolen et al (2021) found that renewable energy technology oppositely affects the risk premium due to the heterogenous influence on risk-related hedging pressures of retailers and producers. Krecar and Gubina (2019) stated that, renewable energy increases market risk, influencing the trading and volatility. Finally, the relationship between financial markets and policy risks is an increasingly important factor for investors in this sector, since the effects of structural modifications, market reforms and new tools to address risk and return issues are essential to investors (Zhang and Farnoosh, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Koolen et al (2021) found that renewable energy technology oppositely affects the risk premium due to the heterogenous influence on risk-related hedging pressures of retailers and producers. Krecar and Gubina (2019) stated that, renewable energy increases market risk, influencing the trading and volatility. Finally, the relationship between financial markets and policy risks is an increasingly important factor for investors in this sector, since the effects of structural modifications, market reforms and new tools to address risk and return issues are essential to investors (Zhang and Farnoosh, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…risk management and trading. In the risk management, prospective energy companies would be focused on MC simulation results to quantify the value of possible loss in the worst-case scenario, [38].…”
Section: G Kgb Linear Model Usementioning
confidence: 99%